Measuring performance of manufacturing listed company based on ROA / Muhammad Faizal Mohd Rasli - Mohd Rasli, Muhammad Faizal (2014)
In this research we want to focus on what factor determining the performance of the manufacturing company listed in Bursa Malaysia. We will be using ROA as indicator to measure the profitability of each of the manufacturing company in Malaysia. The first objective of this research is that we want to investigate the relationship between IV and DV in this case the DV is the profitability( ROA) and the possible IV are size, technology, age, capital structure, Tax, Capital ratio and advertising cost. The second objective is that we want to know which one of the possible IV mentioned is the most dominant towards the DV. Time frame for this research is to be at ten years worth of data and the target company is the manufacturing company listed in Bursa Malaysia using panel data. The data are collected from Osiris and gather according to the availability of the data. The data are collected from year 2003 until 2012 which comply ten years worth of data from 53 selected manufacturing companies listed in Bursa Malaysia